Rice Demfarm Financing Model in Trial Of Excelent Variety on New Operating Land Cooperation Between Stakeholders and Partners - Yuwinti Nearti; Budi Fachrudin; Nirmala Jayanti (Sriwijaya Journal of Environment, 2022)
Rice productivity can be increased by expanding the number of inputs or through the application of new technologies. Demonstration Farm (Demfarm) is one of the methods used for the adoption of agricultural technology according to the developed potential commodities. This study intended to determine the financing model for lowland rice located in Sungai Dua Village, Rambutan District, Banyuasin Regency based on the variety used in relation to rice field construction. The method used was a trial or experiment. This research was conducted on an outdoor laboratory area of the University of South Sumatra in collaboration with partners (IPB University, PT ATS Inti Sampoerna, PT PUSRI, BPTP). There are 3 superior varieties used consisting of IPB3S, Inpari 32 and Ciherang covering an area of 6 hectares in 2021. The population of this study are all farmers who participate in the new rice field printing program that will be formed into the Rice Estate Community (KEP), as many as 15 people who own land and farm laborers by using the census method considered that the entire population as the sample. The analysis used is qualitative and quantitative analysis. The results showed that the income earned by the University of South Sumatera in the first period was Rp.(7,3977,235)/0.5 Ha/MT for the IPB3S variety, Rp.(6,638,485)/0.5 Ha/MT for the IPB3S variety. Inpari 32 and p(5,949,235) /0,5 Ha/MT for Ciherang variety. Constraints faced were soil pH <4, pH of water between 2-3 and still contains pyrite, shallow swamp land type endanger to flooding, inappropriate irrigation and land conditions that still had a lot of tree trunks left. The feasibility analyses used were the B/C ratio and R/C ratio, the results of which showed that based on superior varieties the B/C ratio for the IPB3S variety was (0.80), the Inpari 32 variety was (0.79 ) and Ciherang variety was (0.74). While the R/C ratio in the IPB3S variety was 0.20, the Inpari 32 variety was 0.21 and the Ciherang variety was 0.24. The B/C ratio and the R/C ratio value < 1 indicated that the activities of this model of financing of new rice farming for the first planting period were not feasible due to natural hazard, technical and inappropriate  facilities. This research showed that the better resistance and adaptation were shown by the Ciherang variety.